1)t4-1/5t2+1/100=0 2)(2z2+11z)2-23(2z2+11z)+126=0  3)(x2-4x+1)(x2-4x+2)=12 

1)t4-1/5t2+1/100=0 2)(2z2+11z)2-23(2z2+11z)+126=0  3)(x2-4x+1)(x2-4x+2)=12 
Гость
Ответ(ы) на вопрос:
Гость
2) пусть 2z^2 +11z = a a^2 - 23a +126=0 a = 9   a = 14 2z^2 +11z = 9 2z^2 +11z-9 = 0 z = -4,5     z = 1   2z^2 +11z = 14 2z^2 +11z - 14 =0 z = -3.5     z   =-2   3) x^2 -4x = a (a+1) (a+2) =12 a^2 +3a +2 = 12 a^2 +3a -10 = 0 a = 2     a= - 5 x^2 -4x = 2 x^2 -4x -2 =0   x^2 -4x = -5 x^2 -4x + = 0  
Не нашли ответ?
Ответить на вопрос
Похожие вопросы